Evaluation of the variations of mandibular molars and the distance from root apex to the inferior alveolar nerve in Saudi Sub-population: Three-dimensional radiographic evaluation - Tariq Mohammed Aqili; Esam Sami Almuzaini; Abdulbari Saleh Aljohani; Ahmed Khaled Al Saeedi; Hassan Abdulmuti Hammudah; Muath Alassaf; Muhannad M. Hakeem (PLoS ONE, 2025)
Aim To investigate the prevalence of various morphological variations in the roots and canals of lower mandibular molar teeth in the Saudi subpopulation and measure the distance from the root apices to the inferior alveolar canal (IAC). Materials and methods A cross-sectional analysis was conducted on 149 CBCT scans from Taibah University the College of Dentistry (TUCD). Three evaluators independently reviewed scans for anatomical features such as the number of canals, the presence of radix molaris (RM), and root-to-IANC distances. Teeth observed from the medullary cavity to the root apical layers on the coronal, sagittal and cross-section views. Data was analyzed using SPSS 21.0 software. Statistically significant differences were defined at p < 0.05. Results The prevalence of RM ranged between 0.7%-3.4% in lower first and second molars. The number of the canals in the apex ranged between 2–4 canals, with most molars showing three canals. The prevalence of 2 canals in lower first molars is around 2% and in lower second molars is 9.2%. A significant age-related correlation was noted in distances from the mesial and distal roots to the IAC, with values ranging from 0 to 14.7 mm. Conclusion The study reveals diverse root and canal morphologies and varying distances to the IANC within the Saudi subpopulation, emphasizing the necessity for precise preoperative radiographic assessments to optimize endodontic outcomes and reduce procedural risks. Findings suggest the need for further research into these anatomical variations to refine diagnostic and treatment strategies in endodontics, particularly in diverse populations to improve patient outcomes.